Optimized MIMO symbol mapping to improve the turbo cliff region of iterative precoded MIMO detection - Nhat-Quang Nhan; Rostaing, Philippe; Amis, Karine; Collin, Ludovic; Radoi, Emanuel (2015 23rd European Signal Processing Conference (EUSIPCO), 2015)
In this paper we investigate the concatenation of the multiple input multiple output (MIMO) max-d min linear precoder with an outer forward error correction (FEC) code assuming turbo detection at the receiver. A maximum squared Euclidean weight (MSEW) binary-to-MIMO symbol mapper is introduced in the precoding scheme. Extrinsic information transfer (EXIT) chart is used to analyze the turbo-cliff and error-floor of the proposed MIMO symbol mapper. Analysis and simulation results show significant improvement of the proposed MSEW symbol mapper in terms of error-rate performance.